(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
Oncological diseases, or cancers, represent one of the leading causes of morbidity and mortality worldwide. Over the years, advances in laboratory diagnostics have significantly improved the early detection, monitoring, and treatment of cancer. The role of laboratory tests in oncology is pivotal, as they provide essential information on tumor biomarkers, genetic mutations, tumor profiling, and response to therapies. This article aims to explore the current state of laboratory diagnostics in oncology, emphasizing the various diagnostic techniques, biomarkers, and future directions in cancer diagnostics.